Private Pictures and Public Secrets: Responding to transgressive soldier-produced imagery in United Kingdom news. (11th June 2018) - Parry, Katy
Abstract : New media technologies present greater opportunities for the unguarded and personalized aspects of war to be shared in public spaces, including an element that militaries prefer remains unseen: the depiction of "our boys" killing. This article examines how soldiers' transgressive visual practices of posing with dead bodies during the war in Afghanistan are re-presented in the mainstream UK press, and analyses the reactions garnered from group interviews with serving military media operations personnel, veterans' groups and forces families. Contradictory impulses are revealed in the news media's outraged revelling in the presumed scandal, and in the focus group participant responses, many of whom reject the premise for the news story whilst also acknowledging common experiences of combat and the desire to show others "what war's like". The article therefore contributes to debates on the news mediation of amateur snapshot images, the imbrication of photographic practices in wartime experience and the limitations of the news media as national moral arbiters. In prioritizing a methodological and analytical focus on the (military) audience rather than the news coverage, the article highlights how engagement with journalistic images and texts can act as a catalyst for identity-affirmation and for thinking critically about the military–media nexus.